Psychological Peculiarities of the Conceptual Activity Model of the Future Informatics Lecturer Formation as One of the Projecting Stages - Smal, O. A. (Psychological Prospects Journal, 2012)
The article is devoted to the problem of projecting investigation of the conceptual activity model of informatics lecturer. The concepts «projecting», «modeling», «conceptual model» are reviewed. The scheme of the conceptual model of the future informatics lecturer’s professional activity, which consists of efficient images totality, is formed.